Work Environment and Job Satisfaction Among Public Primary School Teachers in Narok Central Division, Kenya - Omwocha, Shem Onsongo; Kara, Augustine; Mutisya, Sammy (International Journal of Scientific Research and Management (IJSRM), 2025)
Teacher discontent characterized by resignations and switching careers puts at risk the pride that has historically been associated with the teaching profession. It affects the overall quality of the education system. Narok Central Division has recorded increasing cases of teachers seeking transfers and resignations as others seek employment opportunities in areas not related to their careers. Such occurrences point to issues with teachers’ job satisfaction which is affected by a range of factors including the work environment. Teachers’ workload and teachers’ perception of learner discipline are salient features in school work environment which have the potential to influence teachers’ job satisfaction in Narok Central Division. This study therefore investigated the effects of teachers' workload and teachers' perception of learner discipline on teachers’ job satisfaction in the Division. The target population was 659 teachers in 73 public primary schools in the Division. Twenty nine (29) schools were sampled. In the schools, 199 (30.0%) teachers were sampled. All the principals in the sampled schools were key informants for the study. Data were collected using a questionnaire for the teachers and an interview guide for the headteachers. To achieve validity, the study conducted a comprehensive literature review to align research instruments with established theories and also piloted the instruments. The Cronbach Alpha coefficient of reliability for the questionnaire was 0.809. Quantitative data were analyzed using descriptive statistics and presented using tables while qualitative data were analyzed using content analysis. Hypotheses were tested using Pearson Product Moment Correlation analysis at p< .05. The study found that teacher’s workload (M=2.96 SD=1.26) had a weak positive but statistically significant correlation with teacher job satisfaction (p=.010, r=.183, n= 199). The teachers' perception of learner discipline (M=4.07 SD=1.26) had a moderate, positive and statistically significant correlation with teachers’ job satisfaction (p=.000, r=.330 n=199). To enhance teacher job satisfaction, the study recommends strengthening work environment factors, particularly by balancing teaching workload and ensuring learner discipline is managed.